Konsep Kebenaran Ibnu Sina - Imron Mustofa (Universitas Darussalam Gontor, 2017)
Truth is an absolute that must be achieved by human beings. It is because there is an element of the human instincts characteristic in the truth; to seek, to understand and to comprehend. Without the truth, human life would lose a barometer of humanity values. There is a problem when a standard of truth is seized by some ideologies which come from human thought. Therefore, this paper tries to research the concept of truth deeper, including the process of its presence and its causes. To shorten the long discussion of the theory of truth, the author of this article tries to focus his research on Ibnu Sina’s theory of the truth. As a great philosopher of Islam, Ibnu Sina has an ideal concept ofepistemology, so it is worthy to be studied. For the theory of truth, Ibnu Sina has an interesting view on it. According to him, the truth is contained in philosophical thinking which he describes as wisdom. He divides it into two main concepts. In addition, he also explains the the relation between the truth and the philosophy built upon three important reasons. This paper also explains the relation between the truth and the concept of mind, which is called kama>l al-awwal in Ibnu Sina’s terms. Further, this study also discusses the relation of intuition with the theory of truth. Ibnu Sina called intuition with some terms, such as ma’rifah, tahsi>l, and mula>hazah